Esperienze di Public History of Education nell$1 (BUniversità di Bologna, tra ricerca scientifica e didatticas - Mirella D$1 (BAscenzos (Firenze University Press, 2019)
The contribution explores the Public History of Education activities carried out at the University of Bologna, characterized by the organization of exhibitions and thematic exhibitions as well as research-training actions with schools, aimed at enhancing the historical-educational heritage and collective school memory.
Keywords: Collective School Memory; School Archives; Public History of Education; Active Didactics; Public History